Scoping of plant nurseries for business incubation in agroforestry - Thomas, Subin; Arunachalam, Ayyanadar; Dev, Inder; S, Suresh Ramanan (Indian Journal of Agroforestry, 2023)
National agroforestry policy of India envisages to promote agroforestry i.e tree-based farming system in the arable lands and degraded/waste-land. For this, the basic requirement is the quality planting material. This warranted the objective of the study to be ascertaining the constraints of the nursery growers on the production of seedlings from mother plant and quality seeds. The primary data collection was done during April to July, 2022, using a structured and semi-structured interview schedule. A sample of 52 nursery growers from various places in Jhansi region (Jhansi city, Bunguagaon and Bharwasagar) were interviewed. Salient features of the interview schedule included farm size, total nursery area, age, education, annual income, experience of the growers. Changes in the mother plant species diversity raised in the nurseries across fruit-based plants species (mango, jackfruit, java plum, pomegranate, guava, gooseberry, lemon and tamarind) and timber-based mother plants (teak, sesame and neem) were recorded. Three aspects emerged as major constraints. As input, the greatest constraint faced by the nursery owner was the non-availability of quality mother plants for preparing root stocks (73.90 %). While the technical difficulties faced by the nursery growers are majorly unavailability of improved machinery (75.60 %), the financial issues faced by the nursery growers included investment, unregulated market and volatility in the price of seedlings (70.60 %). Thus, institutional support like the agroforestry business incubation centre is a call for bridging and addressing these difficulties, and enable an ecosystem centered around plant nurseries as a business opportunity in agroforestry.